THE INFLUENCE OF TRAINING NEEDS ASSESSMENT, TRAINING DESIGN, TRAINING DELIVERY STYLE, AND TRAINING EVALUATION ON EMPLOYEE PERFORMANCE AT PERUMDA TIRTANADI - Dedy Widarta; Rulianda Purnomo Wibowo; Meilita Tryana Sembiring (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of training on employee performance at Perumda Tirtanadi, a regional-owned company engaged in public water services in North Sumatra. The research applies a quantitative associative approach to examine the influence of four key dimensions of training training needs assessment, training design, training delivery style, and training evaluation on employee performance. Data were collected through questionnaires distributed to employees across several divisions of Perumda Tirtanadi and analyzed using multiple linear regression with SPSS. The results show that training has a significant positive effect on employee performance, both partially and simultaneously. Each dimension of training contributes differently, with training design and training evaluation showing the strongest influence. These findings indicate that a systematic and well-evaluated training program can enhance employees’ competence, productivity, and service quality. The study emphasizes the importance of continuous human resource development and provides practical recommendations for improving the effectiveness of training programs within public sector organizations.